24.7k views
5 votes
3(x-6)+6=5x-6 useing distributive property

1 Answer

3 votes

Answer:

x=-3

Explanation:

3(x-6)+6=5x-6 - Problem

The Distributive property says a(b+c)=ab+ac. Using this knowledge, lets solve.

1) Distribute 3 to x and -6:

3x-18+6=5x-6

2) Combine alike terms: (-18 and 6)

3x-12=5x-6

3) Subtract 3x from both sides:

-12=2x-6

4) Add 6 to both sides:

2x=-6

5) Divide both sides by 2:

x=-3

User Tomo Huynh
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.